(3GdJYdd HQShe GdESfGO HYO EfJbGd Cgd GdefRd hGdfGOs - (3eMeO Hf CMeO Hf eMeO Hf eMeO Hf Ydj Hf ZGRj GdYKeGfj GdecfGSj , GHf ZGRj , CHh YHO Gddg,J (B919 (3g` s ((3JdeSGf s)
(3ChdgG (B:s
(3GdMeO ddg SHMGfg Mb MeOg CeG HYO abO hUd EdjfG ef eOjfI JdeSGf CQHYI cJH WdHhG ajgG ELGRJge HeQhjGJg , aCLGHge ai gPG GdcJGH Edi WdHge s
(3BNQgG (B:s
(3hbO CLRJ ddSGOI GdCcQejf GdeSJOYjf ddELGRI ai UOQ gPG GdeLehY LejY eG ETJed Ydjg , hLejY eG jUM di hYfi QhGjJg hBNQ OYhGfG Cf GdMeO ddg QH GdYGdejf s
(3HgG ELGRI HJGQjN (B890 (3g`s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B336 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B16 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B226s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs